Effect of a Pleuran-Based Supplement on Salivary IgA Secretion in Children With Recurrent Respiratory Infections - Peter Kunc, MD, PhD; Jaroslav Fabry, MD, PhD; Michaela Matiscakova, MD; Katarina Istvankova, DVM; Zuzana Diamant, MD, PhD; Juraj Majtan, PhD, DSc; Milos Jesenak, MD, PhD (Current Therapeutic Research)
Background: ß-glucans isolated from natural sources have demonstrated pluripotent immunomodulatory potential, making them a promising supportive treatment for the management of recurrent respiratory infections (RRIs) in children. This study aimed to evaluate the effects of a pleuran-based supplement (ß-glucan isolated from Pleurotus ostreatus in combination with vitamin D and zinc) on mucosal immunity –through modulating salivary secretory immunoglobulin A (sIgA) levels –in children with RRIs. Methods: This monocentric, prospective, open-label pilot study investigated the effect of an orally administered pleuran/vitamin D/zinc supplement (1–2 chewable tablets daily depending on body weight) on the dynamics of sIgA secretion measured in saliva samples collected at three timepoints: at baseline and after 4–6 and 8–10 days. Results: This study included 49 children aged 6-11 years (mean age: 8.2 ± 1.6 years) with a history of one or more of the following conditions in the inclusion criteria: RRIs, allergy, and asthma. After 8–10 days with daily administration of the chewable pleuran/vitamin D/zinc supplement, children exhibited a statistically significant increase in salivary sIgA concentrations compared with baseline (227 ± 211 µg/mL; P = 0.045). No adverse events were observed during the course of the study in relation to the administration of pleuran-based supplement. Conclusions: We demonstrated the beneficial effects of the short-term administration of a pleuran-based chewable supplement on mucosal immunity through increasing salivatory sIgA levels. This study confirms the favourable safety profile of this pleuran/vitamin D/zinc combination, which could be beneficial for children with acute or recurrent respiratory infections, including children with allergies and/or asthma. Moreover, the significant increases in salivary sIgA concentrations that were observed after a few days of supplementation support the use of pleuran in not only the prevention but also the treatment of acute respiratory infections.